Characterizing reactions and fate of trace elements in the Amazon biome and marine environments by combining chemical speciation and isotopic analyses - Prianti, Marcelo Tesser Antunes (2025)
Trace metals play a fundamental role in biogeochemical cycles, influencing environmental processes in marine and terrestrial ecosystems. This thesis investigates the geochemical dynamics of chromium (Cr), manganese (Mn), zinc (Zn), and mercury (Hg) across different environmental matrices, focusing on their sources, transformations, and fate. Using a combination of advanced analytical techniques, including X-ray Absorption Fine Structure (XAFS) spectroscopy and stable isotope geochemistry, this research challenges conventional paradigms of trace metal cycling and provides novel insights into their environmental behavior. The first study examines Cr speciation in reducing marine sediments and black shales, demonstrating that Cr(III) bound to natural organic matter (Cr(III)-NOM) represents a significant burial phase previously overlooked in paleo-redox reconstructions. The second study utilizes Hg isotopes to trace contamination sources from artisanal and small-scale gold mining (ASGM) in the Brazilian Amazon. The results reveal distinct Hg isotope fractionation pathways associated with atmospheric deposition and mining activities, providing a robust framework for distinguishing natural and anthropogenic Hg inputs. The third study investigates Mn and Zn speciation in highly weathered tropical soils. XAFS analyses reveal the critical role of NOM in stabilizing Mn/Zn in tropical environments. Overall, this research refines our understanding of trace metal biogeochemistry in marine and tropical soils settings, offering new perspectives on their environmental fate and cycling.